(untitled) (Journal of the College of Education for Women, 2019)
The relationship between the elements of the climate and the productivity of citrus (kg/ tree) in the province of Karbala has been determined through the use of simple correlationcoefficient of Pearson (rp) and (t) test. The result for each of oranges, limes and tangerine hadall shown moral and relevant statistical indications; except for relative humidity, which werenot linked to a moral relationship with productivity of tangerine, oranges and limes.As for therelationship between climatic factors and yield of bitter orange were all not significantstatistically and very weak.In order to determine the strength of the correlation between fluctuations in theclimatic elements and fluctuations in the productivity of citrus, the researcher has resorted tomeasure the “regression coefficient” (b) between the two variables. The value of (b)calculated for the relationship between fluctuations in hours of sunshine, maximumtemperatures, minimum temperatures and wind speed, compared to the fluctuations in theproductivity